Pri smORF Peptides Are Wide Mediators of Ecdysone Signaling, Contributing to Shape Spatiotemporal Responses - Dib, Azza; Zanet, Jennifer; Mancheno-Ferris, Alexandra; Gallois, Maylis; Markus, Damien; Valenti, Philippe; Marques-Prieto, Simon; Plaza, Serge; Kageyama, Yuji; Chanut-Delalande, Hélène; Payre, François (Frontiers in Genetics, 2021)
There is growing evidence that peptides encoded by small open-reading frames (sORF or smORF) can fulfill various cellular functions and define a novel class regulatory molecules. To which extend transcripts encoding only smORF peptides compare with canonical protein-coding genes, yet remain poorly understood. In particular, little is known on whether and how smORF-encoding RNAs might need tightly regulated expression within a given tissue, at a given time during development. We addressed these questions through the analysis of Drosophila polished rice (pri, a.k.a. tarsal less or mille pattes), which encodes four smORF peptides (11–32 amino acids in length) required at several stages of development. Previous work has shown that the expression of pri during epidermal development is regulated in the response to ecdysone, the major steroid hormone in insects. Here, we show that pri transcription is strongly upregulated by ecdysone across a large panel of cell types, suggesting that pri is a core component of ecdysone response. Although pri is produced as an intron-less short transcript (1.5 kb), genetic assays reveal that the developmental functions of pri require an unexpectedly large array of enhancers (spanning over 50 kb), driving a variety of spatiotemporal patterns of pri expression across developing tissues. Furthermore, we found that separate pri enhancers are directly activated by the ecdysone nuclear receptor (EcR) and display distinct regulatory modes between developmental tissues and/or stages. Alike major developmental genes, the expression of pri in a given tissue often involves several enhancers driving apparently redundant (or shadow) expression, while individual pri enhancers can harbor pleiotropic functions across tissues. Taken together, these data reveal the broad role of Pri smORF peptides in ecdysone signaling and show that the cis-regulatory architecture of the pri gene contributes to shape distinct spatial and temporal patterns of ecdysone response throughout development.